Os custos de transação da cadeia produtiva do biodiesel à base de soja no Rio Grande do Sul: impactos sobre a gestão das cadeias de suprimentos das usinas instaladas - Oliveira, Sibele Vasconcelos de (2010)
This research aims to identify and assess the main sources of transaction costs of the productive chain of soy biodiesel in Rio Grande do Sul and how they affect the management of supply chains of organizations. To do so, proceeded with semi-structured interviews and visits to four plants in operation in Rio Grande do Sul state. It is diagnosed that the main transaction costs involve post-transaction disputes arising from the quality of raw material and non-compliance with deadlines; barriers to collective planning, operational costs, payout policy of firms and opportunistic actions by officials economic. The likely sources of transaction costs include the characteristics of production and marketing of raw soybeans, the level of technology employed by farmers, the pattern of relationships established between different stakeholders and the volume of production demanded by plants. It is observed that the perceptions and expectations of respondents are part of coherent structures with the supply chain structure, that is, it appears that greater the vertical integration of the production process of biodiesel, more positive the results of individual actions seeking to minimize the uncertainty and greater information sharing, the frequency of transactions and loyalty between business partners. It appears, from the interviews that some of the main barriers to the productive chain of soy biodiesel in Rio Grande do Sul are related to the instability of the price of soybeans and their production characteristics, farmers culture and excessive legal bureaucracy. It is expressed the need for such productive arrangement to define tools to converge the different interests, considering the flow of information existing on the balance of production in its different aspects, the articulation of public policy and environmental aspects of production, which converge to the balance between the known conditions of production and adoption of environmentally sustainable practices. Thus, it is emphasized that the application of fuzzy theory to the study of transaction costs nurtures it as a potential tool for the analysis of socioeconomic relations.